1993
DOI: 10.1901/jaba.1993.26-293
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive and Experimental Analyses of Variables Maintaining Self‐injurious Behavior

Abstract: Independent descriptive (correlational) and functional (eqxrimental) analyses were conducted to determine the extent to which the two methods would yield data supporting similar condusions about variables maintaining the self-injurious behavior (SIB) of 6 subjects. For the descriptive analyses, subjects were observed in their residences and at training sites at various times each day while observers recorded naturally occurring sequences of specified subject and staff behaviors. The subjects also participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 30 publications
8
190
1
4
Order By: Relevance
“…Previous research has evaluated the predictive qualities of descriptive assessments (Lerman & Iwata, 1993, Thompson & Iwata, 2007 and found low levels of correspondence between descriptive assessments and functional analyses of severe problem behavior, such as self-injury and aggression (see Thompson & Borrero, 2011, for a review). Although, to our knowledge, such correspondence has not been formally evaluated with food refusal, previous studies have shown that the consequences evaluated during functional analyses of IMB do closely link to typical caregiver responses Piazza, Fisher, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has evaluated the predictive qualities of descriptive assessments (Lerman & Iwata, 1993, Thompson & Iwata, 2007 and found low levels of correspondence between descriptive assessments and functional analyses of severe problem behavior, such as self-injury and aggression (see Thompson & Borrero, 2011, for a review). Although, to our knowledge, such correspondence has not been formally evaluated with food refusal, previous studies have shown that the consequences evaluated during functional analyses of IMB do closely link to typical caregiver responses Piazza, Fisher, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly cited limitations of functional analyses are the fact that they may be lengthy (Applegate, Matson, & Cherry, 1999;Durand & Crimmins, 1988;Pyles, Riordan, & Bailey, 1997;Sturmey, 1994) and that their implementation may require a considerable amount of training and clinical expertise (Crawford, Brockel, Schauss, & Miltenberger, 1992;Durand & Crimmins, 1988;Spreat & Connelly, 1996;Sturmey, 1994). Although conducting a functional analysis is a more lengthy process than is administering a questionnaire, it is not necessarily any more time consuming than is performing a descriptive analysis (Lerman & Iwata, 1993). Furthermore, recent research has yielded several ways for increasing the efficiency of functional analyses by conducting either fewer (Northup et al, 1991) or briefer (Wallace & Iwata, 1999) sessions.…”
mentioning
confidence: 99%
“…However, given the sporadic nature of low rate behavior, these alternative assessments are unlikely to reveal a behavioral function for low rate behavior. Research generally suggests that results of descriptive analyses and indirect assessments are not sufficient to identify behavioral function (e.g., Lerman & Iwata, 1993;Mace & Lalli, 1991 the MFA may actually be easier to implement in a naturalistic setting (e.g., school) than the SFA because the analysis can be conducted amidst daily activity. Future research should replicate and extend these procedures in less intensive settings to demonstrate the assessment's utility.…”
Section: Discussion and Recommendations For Practitionersmentioning
confidence: 99%